Microcrystalline silicon-carbon composite material as well as preparation method and application thereof

By generating microcrystalline silicon-carbon composite materials in a strongly polar solvent using a three-electrode electrolysis method, the safety risks and performance deficiencies of existing silicon-carbon anode materials are solved, and a high-efficiency, low-cost preparation process is achieved, which is suitable for lithium-ion battery anode materials.

CN121065716AActive Publication Date: 2025-12-05CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511615071.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2025-12-05
Estimated Expiration
2045-11-06

AI Technical Summary

Technical Problem

Existing methods for preparing silicon-carbon anode materials suffer from high safety risks, high costs, low initial efficiency, and low capacity. In particular, the use of silanes as raw materials can easily lead to explosions, and the residual organic ammonium salts affect the material's performance.

Method used

A three-electrode electrolysis method is used to add alkylsilanes or haloalkylsilanes to a strongly polar solvent, combined with an inorganic electrolyte such as LiCl, to generate microcrystalline silicon-carbon composite materials through electrolysis. This avoids the use of organic electrolytes and high-voltage coating. The electrolysis conditions are controlled at -2.0 to -5.0V, followed by carbonization treatment.

Benefits of technology

A microcrystalline silicon-carbon composite material with high safety, low cost, and easy industrialization has been developed. It has high initial coulombic efficiency and capacity, requires no extensive cleaning, has good adaptability, and good downstream compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121065716A_ABST
    Figure CN121065716A_ABST
Patent Text Reader

Abstract

The invention discloses a microcrystalline silicon-carbon composite material as well as a preparation method and application thereof, a slice electrode or a solid electrode is used as a working electrode, an inorganic electrolyte is added into a strong polar solution, and then alkylsilane or halogenated alkylsilane is added to prepare an electrolyte; a reference electrode and a counter electrode form a three-electrode electrolytic tank system for electrolysis, the voltage ranges from-2.0 V to-5.0 V, the working electrode is cleaned with an organic solvent after electrolysis is finished, and the microcrystalline silicon-carbon composite material is obtained after drying and carbonization. According to the prepared negative electrode material, a scanning electron microscope equipped with an energy dispersion X-ray spectrometer is adopted to perform point analysis on a specific micro-area of the microcrystalline silicon-carbon composite material, the content of silicon deposited between porous carbon is greater than or equal to 50%, and the content of silicon deposited in carbon particles is less than or equal to 10%. The prepared composite material is high in capacity and first coulombic efficiency, safe in preparation process, low in cost and easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of battery negative electrode materials, and particularly relates to a silicon-carbon composite material and a preparation method and application thereof. BACKGROUND

[0002] The preparation methods of the silicon-carbon negative electrode material commonly used in the industry at present include sand milling and chemical vapor deposition. The former forms silicon-carbon material mainly showing the characteristics of crystalline silicon, and the latter forms material mainly showing the characteristics of amorphous silicon. Crystalline silicon as a negative electrode generally has the characteristics of high initial efficiency, and amorphous silicon has the characteristics of small expansion and good cycle.

[0003] The main material for preparing the silicon-carbon of amorphous silicon by chemical vapor deposition is silane and porous carbon. The silane has very active chemical properties, and a slight leakage will cause explosion, which is very dangerous in production. In order to solve this problem, Chinese patent application CN 119340347A discloses a porous carbon loaded nanosilicon negative electrode and a preparation method thereof. The silicon-carbon negative electrode material is prepared by using a two-stage electrochemical method, hoping to reduce the danger caused by high-temperature cracking of silane, and certain effect has been achieved. However, the method has the following disadvantages: the raw material needs to use expensive ionic liquid, which is difficult to industrialize; the supporting electrolyte uses organic ammonium salt, and the residual ammonia nitrogen will affect the initial efficiency of the material; and ultrahigh voltage is needed for coating, which is difficult for the conductive metal foil to withstand. The prepared amorphous silicon-carbon negative electrode material has low capacity and initial efficiency. SUMMARY

[0004] In order to overcome the problems in the prior art, the application provides a microcrystalline silicon-carbon composite material and a preparation method and application thereof. The prepared composite material has high capacity and initial coulombic efficiency, the preparation process is safe, the cost is low, and the industrialization is easy.

[0005] To solve the above technical problems, the technical solution provided by the application is as follows: The application provides a preparation method of a microcrystalline silicon-carbon composite material, comprising the following steps: S1, preparing a working electrode.

[0006] S2, adding an electrolyte into a strong polar solvent, and then adding alkylsilane or / and halogenated alkylsilane to configure an electrolyte; the strong polar solvent is a solvent capable of dissolving alkylsilane or halogenated alkylsilane and not reacting with the same.

[0007] S3, using the working electrode in S1, the electrolyte in S2, a reference electrode and a counter electrode to assemble a three-electrode electrolytic cell system for electrolysis, and the voltage is-2.0 to-5.0V.

[0008] S4, after the electrolysis is completed, the working electrode is cleaned with an organic solvent, and the microcrystalline silicon-carbon composite material is obtained after carbonization.

[0009] In the present application, the addition of alkylsilane or halogenated alkylsilane in a strong polar solvent facilitates the dissolution of the silicon source, and then the electrolyte is prepared by adding an electrolyte. The electrolyte is electrolyzed by using a three-electrode system. Under the voltage condition of-2.0 to-5.0 V, microcrystalline silicon can be generated on the electrode of the working electrode. After carbonization, the electrolyte that is not cleaned and a part of the light components decomposed in the electrolysis process can be removed, and a microcrystalline silicon-carbon composite material with high initial coulombic efficiency can be obtained. If the voltage is greater than-5.0 V, the strong polar solution in the electrolyte will decompose. If the voltage is less than-2.0 V, the electrolysis power will be insufficient, and microcrystalline silicon cannot be generated at the electrode.

[0010] As an optional embodiment, in the preparation method provided by the present application, in S1, the porous material matrix is mixed with the binder and then coated on a metal conductive plate or a carbon graphite material conductive plate to prepare the working electrode.

[0011] As an optional embodiment, in the preparation method provided by the present application, in S1, the porous material is mixed with the binder to prepare a growing strip-shaped or cylindrical working electrode.

[0012] As an optional embodiment, in the preparation method provided by the present application, in S1, the porous material is selected from one or both of porous carbon and porous graphite.

[0013] As an optional embodiment, in the preparation method provided by the present application, in S2, the electrolyte is selected from one or more of LiCl, NaCl, KCl, LiClO, NaClO, KClO, LiClO4, NaClO4, KClO4, LiBr, NaBr, and KBr.

[0014] The electrolyte in the prior art uses an organic ammonium salt electrolyte, such as tetrabutylammonium chloride, tetrabutylammonium bromide, etc. The organic electrolyte and its decomposition products of this type will remain in the sample and cannot be cleaned, thereby affecting the initial efficiency. At the same time, the residual organic ammonium salt is an impurity that will react with the electrolyte of the lithium ion battery, thereby producing gas and affecting the cycle. The inorganic electrolyte used in the present technology does not leave organic light components, and in the later application of silicon-carbon materials, it can also be used as the electrolyte of the lithium ion battery, which is a beneficial additive, and thus the initial efficiency can be improved.

[0015] Further, LiCl is preferred.

[0016] As an optional embodiment, in the preparation method provided by the present application, in S2, the concentration of the electrolyte in the electrolyte is 0.01 to 0.3 mol / L.

[0017] The concentration of the electrolyte is controlled to be 0.01-0.3 mol / L, which is beneficial to the dissolution of the electrolyte.

[0018] Further, the concentration is preferably 0.1 mol / L.

[0019] As an optional embodiment, in the preparation method provided by the application, in S2, the chemical formula of the alkylsilane is R n SiH 4-n wherein R represents an alkyl group, n represents the number of the alkyl groups connected to the silicon atom, and n is 1-4.

[0020] Further, the alkylsilane is preferably propylsilane or tetramethylsilane.

[0021] As an optional embodiment, in the preparation method provided by the application, in S2, the chemical formula of the halogenated alkylsilane is R a X b SiH 4-(a+b) wherein R represents an alkyl group, X represents a halogen atom, a represents the number of the alkyl groups, b represents the number of the halogen atoms, and a≥0, b≥1, a+b≤4.

[0022] Further, the halogenated alkylsilane is preferably SiCl4 or SiHCl3.

[0023] As an optional embodiment, in the preparation method provided by the application, in S2, the concentration of the alkylsilane or the halogenated alkylsilane in the solution is 0.1-0.8 mol / L.

[0024] In the application, the concentration of the alkylsilane or the halogenated alkylsilane is controlled to be 0.1-0.8 mol / L, which is beneficial to the dissolution of the silicon source. Further, the concentration of the alkylsilane or the halogenated alkylsilane is preferably 0.5 mol / L.

[0025] As an optional embodiment, in the preparation method provided by the application, in S2, the strong polar solvent is selected from one or more of propylene carbonate solution (PC), N-methyl pyrrolidone solution (NMP), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene glycol dimethyl ether (DME), ethyl acetate (EA), methyl propionate (MP), 1,3-dioxolane (DOL), dimethyl formamide (DMF), dimethyl acetamide (DMAc), acetonitrile (CH3CN), dimethyl sulfoxide (DMSO), hexamethyl phosphoramide (HMPA), methyl ethyl ketone (MEK), dichloromethane (CH2Cl2), chloroform (CHCl3) or tetrahydrofuran (THF).

[0026] The strong polar solvent in the application is beneficial to the dissolution of the silicon source, and can more easily promote the generation of microcrystalline silicon.

[0027] As an optional implementation, in the preparation method provided by the application, in S4, the carbonization temperature is 200-400 DEG C.

[0028] In the application, the carbonization temperature is controlled to be 200-400 DEG C, and the residual organic solvent and light components will decompose and escape at this temperature range, further improving the initial efficiency of the material. If the temperature is lower than this range, the light components and organic solvent cannot be completely volatilized, and if the temperature is higher than this range, the generated microcrystalline silicon material will grow rapidly into a crystal silicon, which is not conducive to the cycle and expansion of the material.

[0029] As an optional implementation, in the preparation method provided by the application, in S4, the working electrode is sequentially cleaned with propylene carbonate solution, alcohol and acetone.

[0030] Based on the same technical concept, the application also provides a microcrystalline silicon-carbon composite material prepared by the above preparation method, which is composed of porous carbon particles and silicon, the silicon is deposited in the interior of the porous carbon particles and between the porous carbon particles, the specific micro area of the microcrystalline silicon-carbon composite material is analyzed by a scanning electron microscope equipped with an energy dispersive X-ray spectrometer, the mass content of the silicon deposited between the porous carbon particles is ≥50%, the mass content of the silicon deposited in the interior of the porous carbon particles is ≤10%, and the silicon deposited between the porous carbon particles is microcrystalline silicon, the grain size of the microcrystalline silicon is 2.0-5.1 nm.

[0031] Based on the same technical concept, the application also provides an application of the microcrystalline silicon-carbon composite material prepared by the above preparation method in a lithium battery negative electrode material.

[0032] Compared with the prior art, the application has the following beneficial effects: (1) The application provides a preparation method of a microcrystalline silicon-carbon composite material, which does not use silane gas in the preparation process, has no explosion risk, and is high in safety compared with the prior art.

[0033] (2) The strong polar solvent added in the preparation process is a substance contained in an electrolyte in the preparation process of a lithium ion battery, is good in adaptability, is good in end compatibility, and more importantly, the strong polar solvent is beneficial to the dissolution of a silicon source and is more conducive to the generation of microcrystalline silicon.

[0034] (3) In the prior art, the crystal silicon has less lattice defects, the combination of lithium ions and silicon is more efficient, the general capacity and initial efficiency are higher, but the cycle and expansion performance is poor. The microcrystalline silicon prepared by the application is opposite to the crystal silicon, and the carbon composite material prepared by the application has high capacity and initial efficiency. The preparation process is environmentally friendly, does not use organic ammonium salt, and does not need to be cleaned with a large amount of solution. The industrialization prospect is sufficient, and expensive ionic liquids are not needed. BRIEF DESCRIPTION OF DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings described below are some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without any creative effort on the basis of these drawings.

[0036] Figure 1 XRD pattern of the microcrystalline silicon-carbon composite material prepared in Example 1; Figure 2 SEM pattern of the microcrystalline silicon-carbon composite material prepared in Example 1; Figure 3 SEM pattern of the microcrystalline silicon-carbon composite material prepared in Example 1; Figure 4 SEM pattern of the microcrystalline silicon-carbon composite material prepared in Example 1; Figure 3 EDS pattern corresponding to the SEM pattern of the microcrystalline silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present application, the following will make a more comprehensive and detailed description of the present application in combination with the drawings of the specification and the preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.

[0038] Unless otherwise defined, all the professional terms used in the following have the same meaning as generally understood by those skilled in the art. The professional terms used in the present application are only for the purpose of describing the specific embodiments and are not intended to limit the protection scope of the present application.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present application can be purchased from the market or can be prepared by the existing method.

[0040] Example 1 The microcrystalline silicon-carbon composite material of the present embodiment is prepared by the following method: A three-electrode electrolytic cell was constructed, using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed binder was coated on the copper foil as the working electrode. Lithium chloride and propylsilane were added to the dimethyl sulfoxide solution to configure a 0.1 mol / L LiCl, 0.5 mol / L propylsilane solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0V was applied using an electrochemical workstation for constant potential electrolysis for 2h, after which the electrode was taken out and washed with propylene carbonate (PC), alcohol, acetone in sequence and dried, and low-temperature carbonization was carried out at 350℃. The microcrystalline silicon-carbon composite material of the present embodiment was obtained.

[0041] Example 2 The microcrystalline silicon-carbon composite material of the present example is prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum as the reference electrode. The porous carbon mixed binder was coated on the copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to the propylene carbonate solution to form a 0.01 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for constant potential electrolysis for 2 h. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0042] Example 3 The microcrystalline silicon-carbon composite material of the present example is prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum as the reference electrode. The porous carbon mixed binder was coated on the copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to the propylene carbonate solution to form a 0.01 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for constant potential electrolysis for 2 h. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0043] Example 4 The microcrystalline silicon-carbon composite material of the present example is prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum as the reference electrode. The porous carbon mixed binder was coated on the copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to the propylene carbonate solution to form a 0.01 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for constant potential electrolysis for 2 h. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0044] Example 5 The microcrystalline silicon-carbon composite material of the present example is prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to configure a 0.3 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0045] Example 6 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to configure a 0.1 mol / L NaCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0046] Example 7 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to configure a 0.05 mol / L LiCl, 0.05 mol / L NaCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0047] Example 8 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and a platinum sheet as the reference electrode. Porous carbon mixed with a binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to form a 0.1 mol / L LiCl, 0.1 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h. After the electrode was removed, it was sequentially cleaned with propylene carbonate (PC), alcohol, and acetone and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material of the present example was obtained.

[0048] Example 9 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and a platinum sheet as the reference electrode. Porous carbon mixed with a binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to form a 0.1 mol / L LiCl, 0.8 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h. After the electrode was removed, it was sequentially cleaned with propylene carbonate (PC), alcohol, and acetone and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material of the present example was obtained.

[0049] Example 10 A microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and a platinum sheet as the reference electrode. Porous carbon mixed with a binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to form a 0.1 mol / L LiCl, 0.5 mol / L SiHCl3 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h. After the electrode was removed, it was sequentially cleaned with propylene carbonate (PC), alcohol, and acetone and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material of the present example was obtained.

[0050] Example 11 A microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to form a 0.1 mol / L LiCl, 0.25 mol / L SiCl4solution, and a 0.25 mol / L SiHCl3solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h. After that, the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0051] Example 12 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to form a 0.1 mol / L LiCl, 0.5 mol / L SiCl4solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -2.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h. After that, the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0052] Example 13 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to form a 0.1 mol / L LiCl, 0.5 mol / L SiCl4solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -5.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h. After that, the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0053] Example 14 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to configure a 0.1 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 4 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 350°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0054] Example 15 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to configure a 0.1 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 200°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0055] Example 16 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. Porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to propylene carbonate to configure a 0.1 mol / L LiCl, 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, and low-temperature carbonization was performed at 400°C. The microcrystalline silicon-carbon composite material of the present example was obtained.

[0056] Example 17 The microcrystalline silicon-carbon composite material of the present example was prepared by the following method: A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was prepared into a vertical strip solid-state electrode as the working electrode. Lithium chloride and silicon tetrachloride were added to an N-methyl pyrrolidone solution to configure a 0.1 mol / L LiCl, 0.5 mol / L SiCl4solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out and sequentially cleaned with PC, alcohol, and acetone and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material of the present example was obtained.

[0057] Example 18 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to a propylene carbonate solution to configure a 0.1 mol / L LiCl, 1.5 mol / L SiCl4solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone and dried, and low-temperature carbonization was performed at 100°C. A microcrystalline silicon-carbon composite material was obtained.

[0058] Example 19 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to a propylene carbonate solution to configure a 0.1 mol / L LiCl, 1.5 mol / L SiCl4solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone and dried, and low-temperature carbonization was performed at 600°C. A silicon-carbon composite material was obtained.

[0059] Comparative Example 1 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on a copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to an ethanol solution to configure a 0.1 mol / L LiCl, 0.5 mol / L SiCl4solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for potentiostatic electrolysis for 2 h, after which the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material was obtained.

[0060] Comparative Example 2 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on the copper foil as the working electrode. Lithium chloride and tetraethyl orthosilicate (TEOS) were added to the propylene carbonate solution to configure a 0.1 mol / L LiCl, 0.5 mol / L TEOS solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied for potentiostatic electrolysis for 2 h using an electrochemical workstation. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material was obtained.

[0061] Comparative Example 3 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on the copper foil as the working electrode. Lithium chloride and tetraethyl orthosilicate (TEOS) were added to the propylene carbonate solution to configure a 0.1 mol / L LiCl, 0.5 mol / L TEOS solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied for potentiostatic electrolysis for 2 h using an electrochemical workstation. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material was obtained.

[0062] Comparative Example 4 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on the copper foil as the working electrode. Lithium chloride and tetraethyl orthosilicate (TEOS) were added to the propylene carbonate solution to configure a 0.1 mol / L LiCl, 0.5 mol / L TEOS solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied for potentiostatic electrolysis for 2 h using an electrochemical workstation. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material was obtained.

[0063] Comparative Example 5 A three-electrode electrolytic cell was constructed using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with binder was coated on the copper foil as the working electrode. Lithium chloride and tetraethyl orthosilicate (TEOS) were added to the propylene carbonate solution to configure a 0.1 mol / L LiCl, 0.5 mol / L TEOS solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied for potentiostatic electrolysis for 2 h using an electrochemical workstation. After that, the electrode was taken out and sequentially cleaned with propylene carbonate (PC), alcohol, and acetone, and dried, and low-temperature carbonization was performed at 350°C. A microcrystalline silicon-carbon composite material was obtained.

[0064] Comparative Example 6 A three-electrode electrolytic cell was constructed, using graphite as the counter electrode and platinum sheet as the reference electrode. The porous carbon mixed with the binder was coated on the copper foil as the working electrode. Lithium chloride and silicon tetrachloride were added to the propylene carbonate solution to configure a 0.1 mol / L LiCl and 0.5 mol / L SiCl4 solution. The solution was poured into the three-electrode electrolytic cell, and a voltage of -4.0 V was applied using an electrochemical workstation for constant potential electrolysis for 2 h, after which the electrode was taken out, washed with propylene carbonate (PC), alcohol, and acetone in sequence, and dried, without low-temperature carbonization. A microcrystalline silicon-carbon composite material was obtained.

[0065] The microcrystalline silicon-carbon composite material prepared in Example 1 was subjected to performance detection, and the XRD pattern is shown in Figure 1 Figure 1 It can be seen that a weak characteristic peak of silicon appears at a position of 28.6° in 2Theta, indicating that microcrystalline silicon is generated. Calculation by the Scherrer formula shows that the grain size of the microcrystalline silicon is 3.6 nm.

[0066] The SEM image of the microcrystalline silicon-carbon composite material prepared in Example 1 is shown in Figure 2 Figure 2 It can be seen that the generated silicon is uniformly distributed between the particles of the electrode sheet. The cross-sectional SEM image of the microcrystalline silicon-carbon composite material prepared in Example 1 is shown in Figure 3 Figure 3 It can be seen that the silicon is deposited both inside the porous carbon particles and between the porous carbon particles. Point analysis was performed on specific microareas of the sample using a scanning electron microscope equipped with an energy dispersive X-ray spectrometer, Figure 3 The EDS image corresponding to the cross-sectional SEM image is shown in Figure 4 Point EDS detection was performed on 1 point between the porous carbons, and the energy spectrum data showed that the mass fraction of Si element in the elemental composition at the point was 90.13%. Point EDS detection was performed on 2 points inside the porous carbons, and the energy spectrum data showed that the mass fraction of Si element in the elemental composition at the point was only 3.97%, indicating that most of the silicon is deposited between the particles, and the silicon content between the particles is more than 50%, while the silicon content inside the particles is less.

[0067] The silicon-carbon materials prepared in the examples and the comparative examples were tested according to “GB / T 38823-2020 Silicon Carbon”, and the test results are shown in Table 1.

[0068] Table 1: Performance detection results of silicon-carbon materials

[0069] ​​​As can be seen from Table 1, the microcrystalline silicon carbon negative electrode material prepared in Example 1 has a silicon grain size of 3.6 nm, a specific capacity of 2215 mAh / g, and a first efficiency of 91.6%, and has the best comprehensive performance. The silicon grain size of the remaining examples is above 2.5 nm, and the specific capacity and first efficiency are above 1600 mAh / g and 85%, respectively. In Comparative Example 18, the silicon source concentration is too large, which causes the solution to separate, low electrolytic efficiency, low capacity, and too low carbonization temperature, resulting in incomplete volatilization of light components and low first efficiency. In Comparative Example 19, the carbonization temperature is too high, resulting in rapid increase of silicon grain size, formation of crystalline silicon instead of microcrystalline silicon, and although the capacity and first efficiency are acceptable, the large grain size will affect the cycle and expansion performance of the silicon carbon material. In Comparative Example 1, the ethanol solvent will react with the halogenated alkylsilane, and the purity and voltage window will be limited, resulting in almost no electrolysis. In Comparative Example 2, without adding electrolyte, the capacity and first efficiency are low. In Comparative Example 3, other ester silicon sources will also affect the capacity and first efficiency. In Comparative Example 4, the high electrolysis voltage will cause abnormal growth of silicon crystals, and the decomposition of the solution will greatly reduce the capacity and first efficiency. In Comparative Example 5, only soaking without electricity cannot form deposited silicon, and only shows the capacity of carbon particles. In Comparative Example 6, without carbonization, there will be more heteroatoms, and the capacity and first efficiency will be reduced.

[0070] The above is a further detailed description of the present application in combination with specific preferred embodiments, and the specific implementation of the present application should not be limited to these descriptions. For ordinary skilled persons in the art to which the present application belongs, without departing from the concept of the present application, a number of simple deductions or substitutions can be made, which should be considered as falling within the protection scope of the present application.

Claims

1. A method for producing a microcrystalline silicon-carbon composite material, characterized by, The method comprises the following steps: S1, preparing a working electrode; S2, adding an electrolyte into a strong polar solvent, and then adding alkylsilane or / and halogenated alkylsilane to configure an electrolyte; the strong polar solvent is a solvent capable of dissolving alkylsilane or halogenated alkylsilane and not reacting with alkylsilane or halogenated alkylsilane; S3, using the working electrode in S1, the electrolyte in S2, a reference electrode and a counter electrode to configure a three-electrode electrolytic cell system to perform electrolysis, and the voltage is-2.0 to-5.0 V; S4, after the electrolysis, cleaning the working electrode with an organic solvent, and obtaining a microcrystalline silicon-carbon composite material after carbonization.

2. The production method according to claim 1, characterized by, In S2, the concentration of the alkylsilane or halogenated alkylsilane in the electrolyte is 0.1 to 0.8 mol / L.

3. The preparation method according to claim 1, characterized in that, In S2, the chemical formula of the alkylsilane is R n SiH 4-n where R represents an alkyl group, n represents the number of alkyl groups attached to the silicon atom, and n has a value of 1 to 4; The halogenated alkylsilane has a general formula of R a X b SiH 4-(a+b) wherein R represents an alkyl group, X represents a halogen atom, a represents the number of alkyl groups, b represents the number of halogen atoms, and a≥0, b≥1, a+b≤4 are satisfied.

4. The method of claim 1, wherein, In S2, the alkylsilane is selected from one or both of propylsilane and tetramethylsilane; and the halogenated alkylsilane is selected from one or both of SiCl4 and SiHCl3.

5. The production method according to claim 1, characterized by, In S2, the strong polar solvent is selected from one or more of propylene carbonate solution, N-methylpyrrolidone solution, ethylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene glycol dimethyl ether, ethyl acetate, methyl propionate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, acetonitrile, dimethyl sulfoxide, hexamethylphosphoramide, methyl ethyl ketone, dichloromethane, chloroform and tetrahydrofuran.

6. The method of claim 1, wherein, In S2, the electrolyte is selected from one or more of LiCl, NaCl, KCl, LiClO, NaClO, KClO, LiClO4, NaClO4, KClO4, LiBr, NaBr and KBr; and the concentration of the electrolyte in the electrolyte is 0.01 to 0.3 mol / L.

7. The preparation method according to claim 1, characterized in that, In S4, the carbonization temperature is 200 to 400 ℃.

8. The preparation method according to claim 1, characterized in that, In S4, the working electrode is sequentially cleaned with propylene carbonate solution, alcohol and acetone.

9. The microcrystalline silicon-carbon composite material produced by the production method according to any one of claims 1 to 8, characterized by The composite material is composed of porous carbon particles and silicon, the silicon is deposited in the interior of the porous carbon particles and between the porous carbon particles, point analysis of a specific micro area of the microcrystalline silicon-carbon composite material is performed by a scanning electron microscope equipped with an energy dispersive X-ray spectrometer, the mass content of the silicon deposited between the porous carbon particles is ≥50%, the mass content of the silicon deposited in the interior of the porous carbon particles is ≤10%, the silicon deposited between the porous carbon particles is microcrystalline silicon, and the grain size of the microcrystalline silicon is 2.0 to 5.1 nm.

10. Application of a microcrystalline silicon-carbon composite material prepared by the preparation method in any one of claims 1 to 8 to a lithium battery negative electrode material.

Citation Information

Patent Citations

  • Preparation method of porous copper based lithium ion battery anode material

    CN103367756A

  • Preparation of amorphous-state film nano silicon electrode material and application in lithium ion battery

    CN106898726A

  • Preparation method of silicon-carbon composite material

    CN113745465A

  • Electrochemical device and electronic device

    CN114420998A

  • Preparation method of silicon-carbon negative electrode composite material

    CN114975946A